Variabilidade e história evolutiva do gene HLA-E - Felício, Leandro Prado (2013)
The HLA-E locus is a Human Major Histocompatibility Complex (MHC) gene associated with immune-modulation and suppression of the immune response by the interaction with specific NK and T cell receptors. The HLA-E gene is considered the most conserved locus in the human HLA; however, this low variability might be a consequence of the scarce number of studies focusing this subject. In this mastering thesis we assessed the HLA-E coding and 3’ untranslated region variability in a group of individuals from Brazil and the results were evaluated together with data from the 1000Genomes Consortium. Altogether, only 28 variation sites were found in approximately 2724 bp evaluated. These variation sites were arranged into 33 haplotypes, most of them (98.2%) encoding one of the two HLA-E molecules found worldwide, i.e., the molecules associated with the allele groups E*01:01 and E*01:03. Interestingly, 85% of all haplotypes were represented by only three different sequences, each of them associated with one of the main known HLA-E coding alleles, E*01:01:01, E*01:03:01 and E*01:03:02, all of them found worldwide. This phenomenon, together with the comparisons with other primate sequences, reveals that these two main allele groups (and molecules) arose early before human speciation, and indicates that E*01:03:01 might be the oldest allele. In addition, the low nucleotide diversity found for the HLA-E coding and 3’UTR in worldwide populations suggests that the HLA-E gene is in fact a conserved gene, which might be a consequence of its key role in the modulation of the immune system.